(untitled) (London,Melbourne, 2005)
Software Evolution with UML and XML provides a forum where expert insights are presented on the subject of linking three current phenomena: software evolution, UML and XML. Software evolution and reengineering are a real problem in the software industry; various attempts have been made in these areas and there is still room for improvement. Tackling evolution with the help of UML and XML can be very beneficial to the software community, especially as the cost of software evolution makes up a considerable proportion, sometimes even 70-80%, of the total budget of a software system.
Keywords: Computer software,UML (computer science),XML (document markup language); Development